A Lyotropic Liquid‐Crystal‐Based Assembly Avenue toward Highly Oriented Vanadium Pentoxide/Graphene Films for Flexible Energy Storage. (15th February 2017) - Liu, Haiqing; Tang, Yanping; Wang, Chi; Xu, Zhixiao; Yang, Chongqing; Huang, Tao; Zhang, Fan; Wu, Dongqing; Feng, Xinliang
Abstract : A novel lyotropic liquid‐crystal (LC) based assembly strategy is developed for the first time, to fabricate composite films of vanadium pentoxide (V2 O5 ) nanobelts and graphene oxide (GO) sheets, with highly oriented layered structures. It is found that similar lamellar LC phases can be simply established by V2 O5 nanobelts alone or by a mixture of V2 O5 nanobelts and GO nanosheets in their aqueous dispersions. More importantly, the LC phases can be retained with any proportion of V2 O5 nanobelts and GO, which allows facile optimization of the ratio of each component in the resulting films. Named VrGO, composite films manifest high electrical conductivity, good mechanical stability, and excellent flexibility, which allow them to be utilized as high performance electrodes in flexible energy storage devices. As demonstrated in this work, the VrGO films containing 67 wt% V2 O5 exhibit excellent capacitance of 166 F g −1 at 10 A g −1 ; superior to those of the previously reported composites of V2 O5 and nanocarbon. Moreover, the VrGO film in flexible lithium ion batteries delivers a high capacity of 215 mAh g −1 at 0.1 A g −1 ; comparable to the best V2 O5 based cathode materials. Abstract : A novel lyotropic liquid‐crystal‐based assembly strategy is developed for the first time to fabricate composite films of vanadium pentoxide nanobelts and graphene oxide sheets with highly oriented layered structures. The resulting films manifest high electrical conductivity, good mechanical stability, and excellent flexibility, which allow them to be utilized as high performance electrodes in flexible energy storage devices.